STRATEGI INTERNASIONALISASI DALAM BIDANG PENELITIAN PADA UNIVERSITAS INDONESIA DAN INSTITUT PERTANIAN BOGOR - Esti Suyanti (Universitas Negeri Jakarta, 2011)
Higher education in Indonesia is faced with increasing international reputation. Rating issued by various international agencies suggested higher education in Indonesia to conduct various strategic initiatives to bring the institution into a World Class University. University of Indonesia and Bogor Agricultural University as the top universities in Indonesia enacted a series of Organizational Strategy and Program Strategies at various fields, including research toward a process of internationalization of higher education. A series of strategies were then examined using a qualitative research approach through a case study of the document search methods, interview and observation. Results from these studies indicate that the awareness of internationalization, international publications and funding as factors that need to be increased in developing areas of research at the University of Indonesia and Bogor Agricultural University. Based on the data analysis model developed Internationalization Strategy, University of Indonesia and Bogor Agricultural University conducted through six forms of support is the awareness, commitment, planning, operationalization, review and reinforcement in a sustainable manner.